2009
DOI: 10.1007/s10517-009-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid on Calcium Signaling in Tumor Cells

Abstract: Effects of ascorbic acid on calcium homeostasis of human laryngeal carcinoma cells were studied. Intracellular concentration of free calcium and intracellular pH were measured by fluorescent analysis. Ascorbic acid in concentrations of 3-10 mM caused pH drop and sharply increased concentrations of free Ca ions in HEp-2 cells. Intracellular concentration of free Ca ions resulted from Ca ion release from the thapsigargin-sensitive Ca depots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In a previous study, ascorbic acid was found to cause a transient increase in [Ca 2+ ] cyt in human larynx carcinoma HEp-2 cells accompanied by depletion of intracellular thapsigargin-sensitive calcium stores [16]. Thapsigargin is known to induce Ca 2+ release, from mitochondria and inositol-1,4,5-triphosphate-responsive Ca 2+ stores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, ascorbic acid was found to cause a transient increase in [Ca 2+ ] cyt in human larynx carcinoma HEp-2 cells accompanied by depletion of intracellular thapsigargin-sensitive calcium stores [16]. Thapsigargin is known to induce Ca 2+ release, from mitochondria and inositol-1,4,5-triphosphate-responsive Ca 2+ stores.…”
Section: Resultsmentioning
confidence: 99%
“…The RET is observed under conditions of high Δ ψ [19]. Previously we have shown that ascorbate at high concentrations induces the decrease in intracellular pH value that can lead to the increase in Δ ψ [16]. In such conditions, rotenone inhibits ROS production in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular calcium is an important signaling molecule for numerous cell responses, including necrosis (Syntichaki and Tavernarakis, ; Li et al, ). It is known that ascorbic acid treatment induces a sharp increment in the cytosolic calcium concentration in tumor cells (Martinovich et al, ). The present study showed that cytosolic calcium levels were increased in Hep2 cells after ascorbic acid treatment and that pretreatment with the calcium chelator BAPTA‐AM dramatically inhibited ascorbic acid‐induced necrotic cell death in these Hep2 cells.…”
Section: Discussionmentioning
confidence: 99%